2019
DOI: 10.1111/1748-8583.12256
|View full text |Cite
|
Sign up to set email alerts
|

Fostering mutual gains: Explaining the influence of high‐performance work systems and leadership on psychological health and service performance

Abstract: Despite the growing importance of sustainable management of human resources, human resource management and leadership research on mutuality in the employment relationship has proceeded in a parallel fashion. Drawing on self‐determination theory, this study proposes an integrative model of human growth by addressing two interrelated questions: (a) how and why experienced service‐oriented high‐performance work systems (HPWS) and unit service leadership relate to psychological health and service performance and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 114 publications
(172 reference statements)
4
94
0
1
Order By: Relevance
“…Moreover, the analysis of Chuang et al (2016) shows that only HRM, not empowering leadership, had main effects on team knowledge acquisition, while the analysis of Hong et al (2016) shows that only HRM, not empowering leadership, had main effects on the initiative climate, even as neither of them focus on these results in their respective studies. Related findings of the relative importance of the main effects of HPWS and leadership can be extracted from Jo et al (2020). We return to discussing the relationships between our study and the joint research on leadership style and HRM in our directions for future research as some of that research has provided conflicting evidence which warrants more discussion (particularly Chuang et al, 2016; Hong et al, 2016; Jiang et al, 2015; Schopman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of Chuang et al (2016) shows that only HRM, not empowering leadership, had main effects on team knowledge acquisition, while the analysis of Hong et al (2016) shows that only HRM, not empowering leadership, had main effects on the initiative climate, even as neither of them focus on these results in their respective studies. Related findings of the relative importance of the main effects of HPWS and leadership can be extracted from Jo et al (2020). We return to discussing the relationships between our study and the joint research on leadership style and HRM in our directions for future research as some of that research has provided conflicting evidence which warrants more discussion (particularly Chuang et al, 2016; Hong et al, 2016; Jiang et al, 2015; Schopman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…First, this study tried to extend the antecedents of thriving by adding perceived leader's helping behavior. Previous research has shown that leadership is one of the key aspects influencing thriving at work (e.g., Li et al, 2016;Xu et al, 2017;Jo et al, 2020). Our research is one of the first studies to bridge the link between perceived leader's helping behavior and thriving at work.…”
Section: Introductionmentioning
confidence: 79%
“…Accounting for thriving at work, we offer a new type of leadership behavior that fosters employees’ thriving. Previous studies have documented that authentic leadership ( Xu et al, 2017 ), empowering leadership ( Li et al, 2016 ), ethical leadership ( Yousaf et al, 2019 ), service leadership ( Jo et al, 2020 ), and many other leaders’ factors (e.g., Frazier and Tupper, 2018 ; Li et al, 2019 ; Yang et al, 2019 ) contribute to increasing employees’ thriving. However, all these studies accounted for between-person variance of thriving at work, and no research addressed the role of leaders’ helping behavior, which is a key part of a leadership role ( Nadler et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the limited amount of studies that focus on the hospitality sector date back to at least ten years (e.g., Chand, 2010 ). More recently, there has been an increasing effort towards revisiting this sector (e.g., Jo et al, 2020 ; Karadas and Karatepe, 2019 ; Ubeda-Garcia et al, 2017 , 2018a , b ), but there is still plenty of ground to be covered. For instance, García-Lillo et al (2018) in their review of Human Resource (HR) studies in the hospitality sector between 1997 and 2016 identified “a gap” in the hospitality HRM literature (p. 1753), and highlighted the need for additional research in investigating the “ mechanisms that lead HR policies and practices to influence unit-level performance through the effects on hotels’ human capital ” (p. 1754).…”
Section: Introductionmentioning
confidence: 99%